Successful treatment of pyoderma gangrenosum with Janus kinase 1/2 inhibition - Sebastian Sitaru; Tilo Biedermann; Felix Lauffer (Wiley, 2022)
Abstract Pyoderma gangrenosum (PG) is a rare, autoinflammatory disease leading to painful, hard‐to‐treat ulcers. Besides systemic glucocorticoids, a plethora of classic immunosuppressants, biologics and small molecules have been reported to improve PG disease course. However, often several treatment strategies fail or cannot be applied due to comorbidities or side effects. We herein report the case of an 85‐year‐old woman with rheumatoid arthritis, lymphopenia and lower leg ulceration due to PG. After multiple steroid‐sparing therapies failed, including methotrexate, mycophenolate mofetil, intravenous immunoglobulins and infliximab, we initiated treatment with baricitinib, a Janus kinase (JAK) 1/2 inhibitor. In combination with intravenous immunoglobulins, we achieved complete remission first of the inflamed margin and second, of the ulceration. Our report suggests that JAK 1/2 inhibition might be a promising therapy option in refractory PG even in elderly patients with comorbidities.